Enhancing the hospitality customer experience of families with children on the autism spectrum disorder (2019)
The purpose of this study is to examine intention to travel to accessible accommodations by families of children diagnosed with autism spectrum disorder (ASD), the influence of travel constraints (intrinsic, interactive, and environmental), the severity of disorder, and the families' strategies for coping with such constraints. A structured survey targeted at Spanish families (N = 117) indicated that the intrinsic dimension and the severity of disorder positively influence their intention to travel. The study contributes to extend knowledge about travel constraints related to accessible tourism and provides insights to accommodation providers on how to better enhance the customer experience of families travelling with a child diagnosed with ASD. © 2019 John Wiley and Sons, Ltd.